Sifat mekanik pada komposit lamina menggunakan matriks kayu mahoni dan reinforcement bambu - Sofyan Djamil; Sobron Lubis; Calvin Chardly Pospos (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
Composite is a combination of two or more materials which creates new property. Composite with basic nature materials is the famous thing now, because hopefully the results of this material composite will strong like iron materials. The method in this research use matrix mahoni wood and woven bamboo for the reinforcement. The research strart with plain woven bamboo and basket woven bomboo cut to size 200mm x 20mm. The next procces bamboo woven is glued with epoxy to fuse macroscopically with wood by hand lay-up. Then this composite materials will be tensile and flexural tested to know the occurred strength. Testing process is done by two methods : tensile test which refers to ASTM 3039 and flexural test which refers to ASTM 7264. Based on tensile test, maximum tensile strength obtained from 5 specimens for Plain Composite specimen about 43,18ð‘ð‘šð‘š2â„, and Basket Composite about 45,65ð‘ð‘šð‘š2â„. Meanwhile, based on flexural test obtained from 3 specimens for Plain Composite woven results in maximum stress about 68,35ð‘ð‘šð‘š2â„ and 82,27ð‘ð‘šð‘š2â„ for basket woven. Results obtained from optical microscope observation shows that fiber from fracture of composite plain woven and basket woven have brittle properties.